(3GdQhV GdCfa hGdeTQY GdQhj aj JaSjQ eG GTJed Ydjg MOjK GdSjQIs - (3YHO GdQMef Hf YHO Gddg GdNfYej GdSgjdj GdCfOdSj, CHh GdbGSe,J (B581 (3g` s ((3eOjfI UfYGA s)
(3ChdgG (B:s
(3EPf Gddg dfHjg Udi Gddg Ydjg hSde HGdgLQI s
(3BNQgG (B:s
(3hPcQ eQGFi MSGf ai GdfHi Udi Gddg Ydjg hSde , djS ajgG eG jTcd afTQMg aUdi Gddg Ydjg hBdg hSde hgh MSHfG hfYe Gdhcjd GfJgi cJGH GdQhV GdCfa s
(3GdLRA GdKGfi ef GdfSNI faSgGs
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG EWGQGJ s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJGQjNs